Življenjski slog starostnikov v Gorenjski regiji na področju duševnega zdravja in preventive pred poškodbami - Zurc, Joca (Obzornik zdravstvene nege, 2012)
Introduction: The aim of the study was to explore the lifestyle of the elderlyin Gorenjska region in respect to two healthy aging factors, injury prevention and mental health. Methods: A cohort of 218 elderly people (>= 65 years) from Gorenjska region (56.9% women, 43.1% men) participated in the study. The data were collected through a structured questionnaire analyzed with SPSS 20.0 software version. Descriptive statistics were used to describe the basic features of the data in the study. Chi-square test, independent samples t-test and one-way ANOVA for testing were employed to determine statistically significant differences between the studied variables (p < 0.05). Results: Results of the study indicate that the respondents are cognizant mainly of only two mental condition, dementia (30.1%) and depression(29.8%), respectively. Statistically significant differences were established as to the source of information in relation to the respondents' place of residence (p = 0.008) and as to whom they would confide their mental health problems, considering the age of the participants (p = 0.008). According to the respondents' opinion, the greatest injury risk factor is carelessness in performing daily activities (81.5%). They experience the biggest fear of injury in winter time (x = 3.80) and when they are alone (x = 3.27). Statistically significant differences were identified in the elderly asconcerns the frequency a particular part of the body is injured, by gender (p = 0.028); in the causes allegedly conducing to injury, by age (p = 0.001) and the educational level (p = 0.008); as to where injury occurs, by age (p = 0.004), and the experience of fear of injury, by age (p = 0.004), educational level (p = 0.021) and place of residence (p = 0.002). Discussion and conclusion: The findings of the present research indicate that health promotion programmes for healthy elderly population should be focused on the area of mental health and injury prevention. Further extensive and in-depth research is needed to collect and analyse the data on lifestyle of the advanced elderly.
Keywords: duševno zdravje; elderly; Gorenjska; health education; health promotion; injury prevention; mental health; preventiva pred poškodbami; promocija zdravja; starostniki; Upper Carniola; zdravstvena vzgoja